ANTIOXIDATIVE EFFECTS OF MAYTENUS DASYCLADA MART. (CELASTRACEAE) - M.SCHWANZ; R.R. DRESCH; V. MANFREDINI; A.T. HENRIQUES (International Journal of Pharma and Bio Sciences, 2013)
Maytenus dasyclada is a trees belonging to the Celastraceae family. The species of Maytenus genus are popularly used to treat gastrointestinal diseases and inflammatory processes as well. The aim of this study was to evaluate the antioxidant activity of hexanic, ethyl acetate and ethanolic extracts from leaves of species, verifying the ability in protect the DNA and remove reactive species, identify and quantify phenolic compounds. The ethyl acetate extracts of species showed the highest amount of total polyphenols (43.65 ± 0.80 mg gallic acid equivalents/g) and the highest content of flavonoids (3.19 ± 0.32 mg quercetin equivalents/g). Quercetin and kaempferol were identified in ethyl acetate and ethanolic extracts. Ethyl acetate and ethanolic extracts of species showed antioxidant activity in the Trolox equivalent antioxidant capacity, in the inhibition of the hydroxyl radical formation, of lipid peroxidation, protein oxidation, and in the protection of damage cellular. The antioxidant activity was related with the antigenotoxic potencial of the extracts. These achieved results showed that extracts of species demonstrated antioxidant activity related to the presence of polyphenols compounds.